The Role of Stock Liquidity in Executive Compensation - Jayaraman, Sudarshan; Milbourn, Todd T. (The Accounting Review, 2012)
ABSTRACT We explore the role of stock liquidity in influencing the composition of CEO annual pay and the sensitivity of managerial wealth to stock prices. We find that as stock liquidity goes up, the proportion of equity-based compensation in total compensation increases while the proportion of cash-based compensation declines. Further, the CEO's pay-for-performance sensitivity with respect to stock prices is increasing in the liquidity of the stock. Our main findings are supported by additional tests based on shocks to stock liquidity and two-stage least squares specifications that mitigate endogeneity concerns. Our results are consistent with optimal contracting theories and contribute to the ongoing debate about the increasing trend of both equity-based over cash-based compensation and the sensitivity of total CEO wealth to stock prices rather than earnings. Data Availability: Data used for this study are derived from publicly available sources.